We were there - Power, Rhoda D. (London : George Allen & Unwin, 1955)
Describes episodes from the tenth to the sixteenth century
Preface. --From the fury of the Northmen... --They called me a scold. --The pilgrimage. --Brother Francis sent us. --Sanctuary. --The surrender of Calais. --The peasants' revolt. --The devil's workshop. --The nine day's queen. --Adventure on London Bridge. --The Spanish Armada
Keywords: Great Britain -- History -- Juvenile literature